INFLUENCE OF CONFLICT MANAGEMENT COUNSELING ON MARRIAGE STABILITY OF COUPLES IN PENTECOSTAL CHURCHES IN KAMPALA, UGANDA. A CROSS-SECTIONAL STUDY. - Nyamahunge Kyokuhaire , Grace; Kiyingi , Frank Pio (Student's Journal of Health Research Africa, 2024)
Background African Traditional Societies systematically initiated boys and girls which prepared them for adulthood experiences like marriage. The study aims to assess the Influence of conflict management counseling on marriage stability of couples in Pentecostal Churches in Kampala, Uganda. Methodology A cross-sectional research design using quantitative approaches to collect data from different categories of respondents at a single point in time. The study employed a descriptive correlation study to determine the relationship between pre-marital counseling and the marriage stability of couples. Results Based on the aggregate mean, conflict management scored a very high aggregate mean of 4.65 and a standard deviation of 0.67. This means that pre-marital counseling in terms of conflict resolution counseling is provided to couples in Pentecostal churches at a very high level. Conflict management counseling has a weak, positive, and significant influence on the marital stability of couples in a Pentecostal church in Kampala City, r = 0.440** which means that conflict management counseling had a positive, weak, and significant influence on marital stability. When the provision of conflict management counseling increases by one unit, the marital stability of couples in Pentecostal churches also changes positively or increases by one unit.However, at a weak level. The fact that the P-value was lower than the significance level (0.000 < 0.05) when r2 was calculated, 0.193 (100), means that conflict management counseling influences positively the marital stability of couples in Pentecostal church in Kampala, Uganda at 19.3%. Conclusion Conflict management counseling had a weak, positive, and significant influence on the marital stability of couples in the Pentecostal church in Kampala Recommendations Churches should continue sensitizing the public on the benefits of pre-marital counseling as the church remains the biggest institution that provides these services to couples.